Study of stress distribution in a cylinder using photo-elasticity method - Rosli, Muhammad Firdaus (2013)
The purpose of this study is to study the stress distribution in a cylinder using photo-elasticity method. The technique comprises from coating selection, design testing method, coating preparation and measure using photo-elastic camera. The coatings that been used were made from epoxy resin. Two different proportion of hardener and resin were used which were PL-3 (3:5) and PL-1 (1:5). Each coating has their characteristics. Two samples were made from steel and aluminium was used. The samples were designed that enabling the stresses to be applied without destroying the plastic coating. Therefore the fringes that representing the stresses could be observed and recorded. The fringes pattern were then been compared with finite element analysis (FEA) software and thus the stress values were calculated. The photo-elastic technique is quite common in some industries particularly in the aircraft industry.